JARINGAN SYARAF TIRUAN UNTUK MEMPREDIKSI LAJU PERTUMBUHAN PENDUDUK MENGGUNAKAN METODE BACPROPAGATION (STUDI KASUS DI KOTA BENGKULU) - Aji Sudarsono (Jurnal Media Infotama, 2016)
This research was conducted to study the neural networks with backpropagation implemented with Matlab. Where data collected through direct observation. And data to be entered are grouped based on factors that influence in predicting the population growth rate. Neural Network was formed by determining the number of units of each layer. Once the network is formed conducted training of the data that has been grouped. The test is conducted with the software Matlab experiments conducted with network architecture that consists of the input unit, the unit hidden layer and output unit. the results obtained from these tests is the value of each architecture Performance and epochs are not equal. The test results are displayed in graphs comparing the target value with the value of training.Keywords: Neural Network Backpropagation, Prediction Population Growth Rate